The power of storytelling: the experiences of incarcerated women sharing their stories - Bove, Andrew (International journal of offender therapy and comparative criminology, 2018)
Women are the fastest growing prison population in the United States. Women who are incarcerated are characterized by significant mental health needs and intense societal stigma. Despite such vulnerabilities, little is known about their experiences or the pathways that lead them toward recovery and rehabilitation. This qualitative research explores the lived experiences of incarcerated women sharing their stories with high school students and their teachers as part of a community outreach project entitled "Stories of Change." Six women were interviewed about what it was like to participate in the project. The data were coded and analyzed using phenomenological techniques, and the results were interpreted through a social constructionist framework. Five themes were revealed through an analysis of the interviews: (a) making a contribution, (b) connecting with others, (c) difficulty of telling their story, (d) identifying personal growth, and (e) moving forward. Storytelling is a powerful experience with lasting effects on the teller. This research explores the phenomenon of storytelling within a context of incarceration and stigma. These findings point toward the importance of providing programming to women within the criminal justice system that allows for meaningful interaction with normative individuals and opportunities for storytelling.